2020
DOI: 10.1029/2019jb018119
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Depth to Bottom of Magnetic Sources Using Spectral Methods: Application on Iran's Aeromagnetic Data

Abstract: The effect of window size while estimating the depth to bottom of magnetic sources (DBMS) is examined on the synthetic 2‐D magnetic field data. The data are generated for 3‐D fractal magnetization models assuming different combinations of depth to the top and bottom of magnetic sources. The depths are estimated assuming an uncorrelated and correlated random distribution of sources. The depths to the top estimated for fractal distribution of sources are found within 70% of the true values for all window sizes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…where ε o and ε t are the standard errors of the crystalline centroid and top depths, respectively 109,110 .…”
Section: Methods Inversion For the Carbonate Top Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…where ε o and ε t are the standard errors of the crystalline centroid and top depths, respectively 109,110 .…”
Section: Methods Inversion For the Carbonate Top Surfacementioning
confidence: 99%
“…The standard error of the top and the centroid depths may be computed separately as 109 : where is the number of observations, and are the observed and estimated values of the corrected power spectrum, and are observed and mean values of the wavenumber considered for depth estimation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard error of the top and the centroid depths may be computed separately as 120 : where is the number of observations, and are the observed and estimated values of the corrected power spectrum, and are observed and mean values of the wavenumber considered for depth estimation. The standard error of the depth to the bottom of magnetic sources and Moho boundary may then be computed using: where and are the standard errors of the centroid and top/crystalline depths, respectively 120 , 121 .…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, fractal magnetization parameter can be used for corrections on the power spectrum (Bouligand et al, 2009;Bansal et al, 2011;Li et al, 2013;Salem et al, 2014;Li et al, 2017;Martos et al, 2018;Kumar et al, 2020;Cruz et al, 2020). On the other hand, Ravat et al, (2007) suggested that the fractal model may yield overcorrection on the RAPS and unreliable results.…”
Section: Curie Point Depth (Cpd) Estimationmentioning
confidence: 99%